Examining the Efficacy of the Baamboozle Application in Improving Students' Vocabulary Proficiency - Ahmad Zulbani; Syafryadin (Journal of English for Specific Purposes in Indonesia, 2025)
Acquiring vocabulary is a crucial aspect of language acquisition as it facilitates conversation, reading, and writing. However, many traditional teaching methods make learning vocabulary feel boring and difficult for students. Students often face problems like forgetting new words easily, lack of practice, and uninteresting lessons. Baamboozle application, a game-based learning tool, might help solve these problems, but there is not much research on its effectiveness. This study aims to find out if Baamboozle application can improve students’ vocabulary better than traditional methods. It also looks at whether using Baamboozle application makes learning more fun and engaging for students. The study was done with seventh-grade students at SMPN Karang Jaya. There were two groups: one group used Baamboozle application, and the other group used traditional methods. Both groups took a test before and after the study to see their vocabulary progress. The results were then compared using statistical analysis. The study found that the Baamboozle application significantly improved students' vocabulary knowledge, as seen by the experimental group's higher average score of 78 compared to the control group's score of 69.83. It showed that the group using Baamboozle application improved their vocabulary more than the group using traditional methods. Students also felt more motivated and interested in learning. This study shows that using game-based tools like Baamboozle application can make learning vocabulary easier and more enjoyable.